Cinnamaldehyde protects against rat intestinal ischemia/reperfusion injuries by synergistic inhibition of NF-κB and p53 - Almoiliqy Marwan; Wen Jin; Xu Bin; Sun Yu-chao; Lian Meng-qiao; Li Yan-li; Qaed Eskandar; Al-Azab Mahmoud; Chen Da-peng; Shopit Abdullah; Wang Li; Sun Peng-yuan; et al. (Acta Pharmacologica Sinica, 2020)
Our preliminary study shows that cinnamaldehyde (CA) could protect against intestinal ischemia/reperfusion (I/R) injuries, in which p53 and NF-κB p65 play a synergistic role. In this study, we conducted in vivo and in vitro experiments to verify this proposal. SD rats were pretreated with CA (10 or 40 mg · kg−1 · d−1, ig) for 3 days, then subjected to 1 h mesenteric ischemia followed by 2 h reperfusion. CA pretreatment dose-dependently ameliorated morphological damage and reduced inflammation evidenced by decreased TNF-α, IL-1β, and IL-6 levels and MPO activity in I/R-treated intestinal tissues. CA pretreatment also attenuated oxidative stress through restoring SOD, GSH, LDH, and MDA levels in I/R-treated intestinal tissues. Furthermore, CA pretreatment significantly reduced the expression of inflammation/apoptosis-related NF-κB p65, IKKβ, IK-α, and NF-κB p50, and downregulated apoptotic protein expression including p53, Bax, caspase-9 and caspase-3, and restoring Bcl-2, in I/R-treated intestinal tissues. We pretreated IEC-6 cells in vitro with CA for 24 h, followed by 4 h hypoxia and 3 h reoxygenation (H/R) incubation. Pretreatment with CA (3.125, 6.25, and 12.5 μmol · L−1) significantly reversed H/R-induced reduction of IEC-6 cell viability. CA pretreatment significantly suppressed oxidative stress, NF-κB activation and apoptosis in H/R-treated IEC-6 cells. Moreover, CA pretreatment significantly reversed mitochondrial dysfunction in H/R-treated IEC-6 cells. CA pretreatment inhibited the nuclear translocation of p53 and NF-κB p65 in H/R-treated IEC-6 cells. Double knockdown or overexpression of p53 and NF-κB p65 caused a synergistic reduction or elevation of p53 compared with knockdown or overexpression of p53 or NF-κB p65 alone. In H/R-treated IEC-6 cells with double knockdown or overexpression of NF-κB p65 and p53, CA pretreatment caused neither further decrease nor increase of NF-κB p65 or p53 expression, suggesting that CA-induced synergistic inhibition on both NF-κB and p53 played a key role in ameliorating intestinal I/R injuries. Finally, we used immunoprecipitation assay to demonstrate an interaction between p53 and NF-κB p65, showing the basis for CA-induced synergistic inhibition. Our results provide valuable information for further studies.